PERAN SPIRITUAL INTELLIGENCE MAHASISWA DALAM MEMATUHI PROTOKOL KESEHATAN - Muh. Luqman Arifin; Ida Zahara Adibah; Muhamad Basitur Rijal; Mahmudin Mahmudin (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2021)
The purpose of this study was to describe and analyze the role of Spiritual Intelligence (SI) and student behavior in complying with health protocols during the COVID-19 period in Indonesia.The research method used is quantitative with descriptive research. The research subjects consisted of 77 students from universities in Indonesia. The data collection technique in this study used a questionnaire technique. The questionnaire was then measured using a Likert scale. The data were analyzed by quantitative descriptive to analyze the students' spiritual intelligence which was illustrated through a questionnaire sheet which consisted of 7 items.The results showed that from 77 students from across study programs from severaluniversities in Indonesia, both male and female, it was found that the average spiritualintelligence level was 4.2 with the "Good" category and there was a positive correlationbetween students' Spiritual Intelligence and adherence to health protocols. during theCovid-19 pandemic.